Effectiveness of ARAM cognitive rehabilitation package on improvement of executive function based on behavioral rating in preschool children with ADHD symptoms - mahdis maghsudloo; vahid nejati; jalil fathabadi (Ravānshināsī-i Afrād-i Istis̠nāyī, 2019)
Executive function deficits are common in children with attention deficit hyperactivity disorder (ADHD). This research aims to assess effects of remedial rehabilitation on executive functions in preschool children with ADHD symptoms. In the current random clinical trial study pretest, posttest and follow-up design with control group were used. Statistical society includes all preschool ADHD children who referred to counselling centers in Tehran between 2016 -2017. Assessments include ADHD symptom checklist-4 (Gadow & Sprafkin, 1998) and Behavioral rating of executive function-preschool (Gioia,epsy& squith, 2002) questionnaires. After initial assessment by ADHD questionnaire, Thirty two children, who significantly had symptoms, selected by accessible sampling and randomly divided in to experimental group (N=15) and control group (N=17). Intervention group received ARAM computerized cognitive rehabilitation program for 12 sessions in 20 minute, while control group received no treatment. Both groups examined in posttest and follow-up. Data analyzed by repeated measure variance analysis. Result showed remediation rehabilitation significantly improves executive function and ADHD symptoms. We can conclude the remedial rehabilitation by computerized tasks improved cognitive abilities and reduced ADHD symptoms in preschool children.